Relationship between nutrition and sleep quality, focusing on the melatonin biosynthesis - SABUNCULAR, GÜLEREN (SPRINGER JAPAN KK, 2020)
Sleep duration and quality are associated with many diseases. Evaluating the relationship between nutrient intake and sleep quality is important, because dietary factors play an important role in sleep quality. Short sleep duration which is associated with both metabolic disorders, obesity and, an irregular sleep pattern are thought to be related to an unhealthy diet. The recent literature has been reviewed using EMBASE, PsycARTICLES, PsycINFO, PubMed, ScienceDirect, and Web of Science databases. The effects of macronutrients and micronutrients on sleep parameters have been demonstrated. Carbohydrates and fats can regulate sleep quality by affecting the duration of Rapid Eye Movement (REM) and non-REM sleep. For proteins, tryptophan is the most promising amino acid for sleep-promoting food, since it is the precursor of melatonin and serotonin playing a role in improving sleep quality of humans. It is a common finding that those who have short sleep duration take in more energy from fat and carbohydrate. However, to what extent diet can affect sleep still remains unclear. This present review discusses the potential role of nutrition in regulating sleep quality and offers suggestions for feasible future studies. Some macro and micronutrients of the diet were found correlated with sleep duration and quality. Mechanisms mediating the relationship between sleep duration and dietary intake are multi-factorial. Therefore, future studies will benefit from assessing sleep duration/quality and dietary intake.
Keywords: Sleep; Sleep quality; Nutrition; Diet; Macronutrients; Micronutrients; ENERGY-EXPENDITURE; DIETARY MACRONUTRIENTS; INSUFFICIENT SLEEP; EATING PATTERNS; DOUBLE-BLIND; FATTY-ACIDS; VITAMIN-D; DURATION; ASSOCIATION; OBESITY